2021
DOI: 10.3390/su13052648
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental, Social Values and the Consideration of Future Consequences for the Development of a Sustainable Entrepreneurial Intention

Abstract: Sustainable entrepreneurship focuses on finding ways to monetize future products, nature conservation, life support, and communities. Therefore, the intention has been identified as one of the key drivers to perceive business opportunities and ultimately leverage them, which increases interest in investigating it, especially from a sustainability perspective. The purpose of this study was to investigate the intention of sustainable entrepreneurship through a modified version of the theory of planned behavior b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 108 publications
3
67
0
2
Order By: Relevance
“…In this sense, social entrepreneurship is interested in promoting sustainable entrepreneurship to foster economic growth and development using differentiating products and services among external stakeholders [17]. As a result, sustainable entrepreneurship focuses on finding ways to monetize future products, nature conservation, life support, and communities [18] with nature preservation and business growth. These promising and fundamental goals do not necessarily imply that positive social or environmental values are being created as a result.…”
Section: Sustainable Entrepreneurship Eco-innovation and Gemmentioning
confidence: 99%
“…In this sense, social entrepreneurship is interested in promoting sustainable entrepreneurship to foster economic growth and development using differentiating products and services among external stakeholders [17]. As a result, sustainable entrepreneurship focuses on finding ways to monetize future products, nature conservation, life support, and communities [18] with nature preservation and business growth. These promising and fundamental goals do not necessarily imply that positive social or environmental values are being created as a result.…”
Section: Sustainable Entrepreneurship Eco-innovation and Gemmentioning
confidence: 99%
“…On the grounds of the conducted pilot research, it needs to be emphasised how important the promotion of an entrepreneurial mindset is, geared not only towards earning profits but also towards sustainable development. The nature of the finding is emphasised by the fact that professed values and social norms have a positive impact on sustainable entrepreneurial intentions [75].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this component, Yasir et al showed through their study that the media's consequences on attitudes towards sustainable entrepreneurship. The authors clearly demonstrated the importance of supporting talent in this field and increasing entrepreneurial skills [70].…”
Section: Entrepreneurship In Vocational and Technical Education In Romaniamentioning
confidence: 93%